The distances covered by basketball referees in a match increase throughout the competition phases, with no change in physiological demand - Borin, J. P.; Daniel, J. F.; Bonganha, V.; Moraes, A. M.; Cavaglieri, C. R.; Mercadante, L. A.; Nolasco da Silva, M. T.; Montagner, P. C. (Open Access Journal of Sports Medicine, 2013)
Background: It is crucial to know the demands on basketball referees, in different match periods (MPs) and phases of competition, for planning referee training and subsequent successful refereeing. Objective: To measure and evaluate the distance covered by referees in a match by measuring the number of interruptions, percentage of heart rate (%HR), and blood lactate concentration ([lac]) in different phases of competition and in different MPs. Method: We studied the qualifying (QP), semifinal (SP), and final (FP) phases of a total of 12 matches (four matches in each phase) of the 2009-2010 Brazilian Basketball League. Distance covered, number of match interruptions, and referees' %HR and [lac] were analyzed. We compared the results between competition phases and between MPs (1st MP, 2nd MP, 3rd MP, and 4th MP). Results: Regarding the distances covered, we observed significant differences (P < 0.05) in the 1st, 2nd, and 3rd MPs between the FP and the other two phases (SP and QP) throughout the match, between each phase; in the 4th MP, a significant difference was found when comparing the QP and the other two phases. Comparing the periods within each phase, we found that a greater distance was covered in the 4th MP in relation to the 3rd MP during the FP. No significant differences were found among the remaining variables. Conclusion: The distances covered by referees in a basketball match increase throughout competition phases. This information is essential for planning of training and for the subsequent success of a referee.